(untitled) (Revista de História da UEG (REVHIST), 2019)
António Oliveira Salazar’s Estado Novo emerged in the period between the wars and lasted until the “Revolução dos Cravos” in April 1974. From its inception, it bears similarities to Adolf Hitler’s regime of German National Socialism and to the fascism of Benito Mussolini. This article seeks to make a discussion of the authoritarian elements of Salazarism, bringing to the light of the discussion the historiography on the subject, mainly in the actions of repression, in the single party, in the groups of youthful youth, in the cult of the leader and censorship. In addition, it we´ll see the opinion of opponents of the regime that taxed the Portuguese regime as fascist in order to compare it with the mentioned dictators and to raise international support.